2000
DOI: 10.1590/s0100-736x2000000100005
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella em carcaças de frango congeladas

Abstract: total de 150 carcaças de frango congeladas, de quatro marcas comerciais, foram analisadas para pesquisa de Salmonella. Foram examinadas 43 carcaças de cada uma das marcas A, B, D e 21 da marca C. Observou-se um percentual de 32,0% de contaminação. Foram identificados 11 sorotipos: S. Agona, S. Anatum, S. Enteritidis, S. Hadar, S. Havana, S. Mbandaka, S. Montevideo, S. Ouakam, S. Poona, S. Schwarzengrund e S. I 4, 5, 12: -. O antibiograma das cepas mostrou 100% de resistência à ampicilina, 75,0% à cefalotina, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
24

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 21 publications
3
35
1
24
Order By: Relevance
“…The total rate of Salmonella contamination of broiler carcasses was 11.8%, which is considered high, The Codex Alimentarius established 0% contamination in 25 g of analyzed food, including poultry meat and eggs (Santos et al, 2000). This percentage is lower than that found by Santos et al (2000), with 32% of contamination; by Machado & Bernardo (1990), with 57% of contamination; by Plummer et al (1995), with 23%; and Arvanitidou et al (1998), with 69%. Our results are consistent with the percentage verified by Sharma (1992), with 9.21% of contamination of broiler carcasses.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The total rate of Salmonella contamination of broiler carcasses was 11.8%, which is considered high, The Codex Alimentarius established 0% contamination in 25 g of analyzed food, including poultry meat and eggs (Santos et al, 2000). This percentage is lower than that found by Santos et al (2000), with 32% of contamination; by Machado & Bernardo (1990), with 57% of contamination; by Plummer et al (1995), with 23%; and Arvanitidou et al (1998), with 69%. Our results are consistent with the percentage verified by Sharma (1992), with 9.21% of contamination of broiler carcasses.…”
Section: Discussionmentioning
confidence: 92%
“…, Lee et al (1993), and Nascimento et al (1997) showed similar results, with 100% of sensitivity to Chloramphenicol in broiler carcasses. Lee et al (1993) and Santos et al (2000) found 100% of resistance to Ampicillin of Salmonella in broiler carcasses. Our results showed that 66.7% of isolates were resistant to Amoxycillin, while Antunes et al (2003) found 19%, 19%, and 3% of resistance to Amoxycillin, Carbenicillin and Chloramphenicol, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Salmonella é um dos mais importantes patógenos mundialmente distribuídos, associado à carne de frango e seus produtos derivados (BRYAN & DOYLE, 1995). Estudos a respeito de prevalência de Salmonella em carcaças de frangos no Brasil, apresentam dados diferenciados, como na cidade de Descalvado, São Paulo, em que o resultado da pesquisa de Salmonella em carcaças foi ausência da bactéria nas amostras (CARDOSO et al, 2005), ou, ainda em São Paulo, porém no município de Jaboticabal, onde 150 carcaças congeladas foram analisadas e o percentual de positividade para Salmonella estabelecido foi 32,0% (SANTOS et al, 2000). Dados do Rio Grande do Sul, apresentados pela pesquisa de NASCIMENTO et al (2003), citam contaminação por Salmonella de 15,1% em carcaças e 26,1% nas amostras de partes de frangos.…”
Section: Introductionunclassified
“…In Brazil, the increase in the incidence of S. Enteritidis from foodborne outbreaks, human infections, non-human sources, broiler carcasses and other poultry materials has been reported since the 90's (5,6,25,29,33,34), and poultry is likely the main source of human infections (10). Typing of bacteria can be used to determine whether isolates recovered from different patients *Corresponding Author.…”
Section: Introductionmentioning
confidence: 99%